247 A COMPARISON OF QUANTITATIVE MEASURES OF MITRAL REGURGITATION SEVERITY WITH QUALITATIVE ASSESSMENT BY AN EXPERT ECHOCARDIOGRAPHIC READER. (1st January 2005) - Gilliss, B. M.; Gerber, I.; Thomas, L.; Crawford, M.; Hoffman, J.; Schiller, N.; Foster, E.
Abstract : Purpose: The clinically important distinction between moderate and severe mitral regurgitation (MR) may be improved by quantitative echocardiographic (echo) measures as suggested by a recent American Society of Echo (ASE) consensus statement. The primary aim of this study is to determine the relative accuracy of 4 quantitative echo measures compared with an expert reader's qualitative assessment of MR severity. Methods: Transthoracic echo's of 62 prospectively enrolled patients (mean age = 61 ± 16 yrs) with MR were graded by expert qualitative assessment as mild (n=25), moderate (n=21) or severe (n=16). Quantitative measures of MR severity including regurgitant fraction (RF), regurgitant volume, vena contracta width and effective regurgitant orifice area were determined by an experienced echo reader blinded to the qualitative assessment. Sensitivity, specificity and area under the receiver operating curve (AUC) were calculated for each quantitative measure to distinguish moderate from severe MR. Data for patients with moderate and severe MR only are described. Results: The causes of MR included myxomatous degeneration (n=13), ischemic cardiomyopathy (n=8), dilated cardiomyopathy (n=7), previous endocarditis (n=2) and other or uncertain (n=7). Sensitivity, specificity and AUC for the quantitative measures using ASE recommended cut points to distinguish moderate from severe MR are shown in the table Conclusions: A RF ≥40% is the most accurate single quantitative measure to distinguish moderate from severe MR as assessed by an expert reader. Measurement of RF in addition to qualitative assessment of MR severity should be considered during management decisions for patients with significant MR.